Peran Perilaku Asertif terhadap Keterampilan Berkomunikasi Remaja - Hanifah, Alifia; Ipah Saripah; Nadia Aulia Nadhira (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
The research aimed to know how the role of assertive behavior on adolescent communication skills. In the development of adolescent the ability to express about theirself directly and their feelings honestly is very important. Adolescents tend to prefer to follow the decisions of their peer group and put aside personal interest. This will certainly have a negative impact if it occurs continously because it can affect their future lives. The method used in this study is a literature study approach by reviewing and analyzing several national and international journals regarding the dynamics of assertive behavior and its role in adolescents’s skill of communication. Based on the results of the descriptive analysis, it was found that the dynamics of assertive behavior has a role that influences each other with adolescent’s skill in communication.